Stability analyses for a large landslide with complex geology and failure mechanism using numerical modelling - Wentzinger, B; Starr, D; Fidler, S; Nguyen, Q; Hencher, S (Slope Stability 2013: Proceedings of the 2013 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2013)
Geotechnical studies were undertaken for a large landslide which occurred during the construction of the South West Transit Corridor, in South East Queensland, Australia. The site investigation revealed complex geology comprising trachyte flows extruded on top of sediments and basalt flows. The evolution of the landslide was monitored using surface survey, inclinometers, piezometers and observation wells. The results of the site investigation, geological mapping, laboratory testing program and monitoring were used to prepare a geotechnical model for stability analyses. The development of the geological and geotechnical models is briefly discussed, and the methodology used to define the failure mechanism and calibrate the model is presented and discussed. Various methods and software packages were trialled in order to model the complex failure, geology and groundwater conditions. The shape of the failure surface was defined using the results of the movement monitoring devices and surface observations of tensions cracks. The assumptions made in defining the failure surface shape and strength properties are presented. The final numerical model was validated using back-analysis with ground water conditions known to trigger movements, and the material properties along the shear surface were compared with the results of laboratory strength tests. The methodology used to estimate the Factor of Safety against reactivation of the movements using numerical modelling is presented. The use of the model to develop remedial measures is also discussed.